The Impact of Friendship Circles on the Self-Confidence of Junior High School Students - Sugiardi, Alfiyah Husna Amalina; Nainggolan, Agnes Stevanny; Dewi, Sukma Ayu Putri Titah; Atmoko, Adi (Proceedings Series of Educational Studies, 2024)
Junior High School students who fall into the middle adolescence category, aged 14-17 years, start searching for their identity as they enter puberty, facing difficulties in making decisions and controlling emotions. At this age, teenagers look for a group of friends who match their interests, hobbies, and lifestyle. The 2024 Teaching Assistance Team from the State University of Malang found that this phenomenon also occurred at the UM Laboratory School, where several students had their own friendship groups, both small and large, encompassing multiple classes. These observed friendship groups had a significant impact worth researching. The aim of this research is to understand the phenomenon of friendship among students and its impact on their self- confidence. The research method used is phenomenological, combining observation, interviews, and documentation. The results reveal that friendship impacts individual students, although differences in perspectives among subjects were also noted.